2019
DOI: 10.3390/ijerph16091541
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Perception, Body Image Dissatisfaction and Their Relations with Weight-Related Behaviors among University Students

Abstract: The prevalence of obesity is increasing globally and is linked with poor body image perception. The aim of the present study was to identify the relationships of body image (BI) and body mass index (BMI) with weight control practices among university students. A cross-sectional study on a sample of 308 university students (150 males and 158 females) aged between 18 and 25 years was carried out. Face-to-face interviews were conducted based on a questionnaire that included socio-demographic, physical activity, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
106
3
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(130 citation statements)
references
References 41 publications
12
106
3
9
Order By: Relevance
“…The practice of physical activity was related to higher weight and shape concern, similarly to ndings of previous research [62,[67][68][69]. Remaining physically active while staying at home for a prolonged period can pose a signi cant challenge to the mental and physical health of individuals.…”
Section: Eating Behaviorssupporting
confidence: 76%
See 1 more Smart Citation
“…The practice of physical activity was related to higher weight and shape concern, similarly to ndings of previous research [62,[67][68][69]. Remaining physically active while staying at home for a prolonged period can pose a signi cant challenge to the mental and physical health of individuals.…”
Section: Eating Behaviorssupporting
confidence: 76%
“…Also, in our study, higher BMI was related to higher eating, weight, and shape concerns. Similarly, other studies had found that higher BMI is a great predictor of weight and shape concern [61][62][63][64].…”
Section: Eating Behaviorsmentioning
confidence: 66%
“…This is because females are reported to usually desire a thinner shape or smaller body size compared to males, who desire a leaner and more muscular shape or larger body size [36,37]. A recent study among university students from the United Arab Emirates (UAE) also found that a higher proportion of females were dissatisfied with their body size, whereby females desired to lose weight and preferred diet to exercise, and males desired to gain weight and preferred exercise to diet [38]. Future DE assessment may need to consider examining compulsive exercise [39] and androgenic anabolic steroid use [40], which may be more prevalent among male young adults.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Body image dissatisfaction reported internationally ranged from 43.9% (using Figure Rating scale) in Moroccan students, 75.49% in Brazil to 81% in UAE (58.2% and 41.8% in males and females respectively) students. [18][19][20] The difference in prevalence can due to the use of different scales/methods to assess body image perception. The difference in demographic characteristics between different regions of India and developed countries can also contribute to the wide array of results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on abnormal body image perception have also mostly concluded that it is seen more in females. [20][21][22][23][24][25][26][27][28] However, Boutahar K did not find any gender difference in body image perception in Moroccan university students. 18 But an interesting finding to note in the present study was that males more than females had an abnormal eating attitude and felt the media pressure to attain an ideal body, the latter being statistically significant (p=0.039).…”
Section: Discussionmentioning
confidence: 99%